The Influence of Customers Communication Behaviour in the Implementation of 21cineplex Viral Marketing Using the Social Networking Site Facebook - Meyliana -; Henry Antonius E.W.; Stephen W. Santoso (CommIT (Communication and Information Technology) Journal, 2015)
Application of viral marketing through social networking sites will greatly help companies in saving high marketing costs since companies do not have to give financial incentive to internet users or customers who voluntarily forward the information about the companies. Good marketing communication strategy will increase the company's branding and enable good interaction between customers and companies. This research to look if the customer communication behavior has a relationship and a significant impact on forwarding online content and whether the curiosity variable has a relationship and a significant impact on the variable of consumption of online content in the application of Viral Marketing. The methodology used is interpersonal communication model adopted from FIRO theory, which consists of the following variables: inclusion-need to belong, inclusion-individuation, affection-altruism, control-personal growth, and consumption of online content, towardthe online content forwarding variable; and also the curiosity variable towards the consumption of online content variable, where the hypothesis was tested by the correlation and regression analysis. The test results based on correlation analysis show that all H1hypotheses (have relation) are received; and based on regression analysis, all H1hypotheses (effect) are received, although the value of r and the effect is less significant (small).